Development of a highly sensitive immunoassay for detecting aminopyrine abuse in herbal tea. Issue 4 (11th January 2023) - Wang, Zian; Liu, Zhiwei; Guan, Tian; Zeng, Xi; Shen, Runlin; Li, Zhaodong; Lei, Yi; Xu, Zhenlin; Xiao, Zhili; Lei, Hongtao; Huang, Dingqiang
Abstract : A sensitive ic-ELISA method for detecting AP in herbal tea was established for the first time and can be used for rapid detection. Abstract : With the popularity of herbal tea in China, many food fraudsters have added illegal drugs to herbal tea to enhance its functions, among which aminopyrine is widely abused as an antipyretic and analgesic. Presently, there is no immunoassays for aminopyrine, and it is difficult to achieve real-time detection in the field. Based on a polyclonal antibody of aminopyrine with high specificity and sensitivity, an optimal combination of coating antigen/antibody was obtained by screening different coating antigens. On this basis, a sensitive ic-ELISA method was established to detect aminopyrine in herbal tea. The detection limit of the ic-ELISA was 0.18 ng mL −1, which was much lower than the 100 ng mL −1 required as a standard. The method had good consistency with LC-MS in the detection of actual samples and could be used as a reliable method for the detection of aminopyrine in herbal tea.